2022
DOI: 10.3389/fonc.2022.989761
|View full text |Cite
|
Sign up to set email alerts
|

Association of genetic ancestry with HER2, GRB7 AND estrogen receptor expression among Colombian women with breast cancer

Abstract: BackgroundOur previous study reported higher mRNA levels of the human epidermal growth factor receptor 2 (HER2)-amplicon genes ERBB2 and GRB7 in estrogen receptor (ER)-positive breast cancer patients with relatively high Indigenous American (IA) ancestry from Colombia. Even though the protein expression of HER2 and GRB7 is highly correlated, they may also express independently, an event that could change the patients’ prognosis. In this study, we aimed to explore the differences in ER, HER2 and GRB7 protein ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…Consistent with our findings, previous studies on the association between genetic ancestry and BC risk in Latin American populations have found differences in BC subtypes by ancestry. Rey-Vargas et al reported a higher proportion of Native American ancestry in Colombian patients with ER+ /HER2+ (45%) than in ER + /HER2− (40%) breast tumours, and Marker et al demonstrated a higher risk of HER2 + BC with increasing proportions of Native American ancestry in Colombian, Mexican and Peruvian women [ 34 , 35 ]. The novelty of the present study lay in the use of instrumental variable analysis to identify and quantify the confounding-free effect of Native American ancestry on the risk of overall BC and BC subtypes.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with our findings, previous studies on the association between genetic ancestry and BC risk in Latin American populations have found differences in BC subtypes by ancestry. Rey-Vargas et al reported a higher proportion of Native American ancestry in Colombian patients with ER+ /HER2+ (45%) than in ER + /HER2− (40%) breast tumours, and Marker et al demonstrated a higher risk of HER2 + BC with increasing proportions of Native American ancestry in Colombian, Mexican and Peruvian women [ 34 , 35 ]. The novelty of the present study lay in the use of instrumental variable analysis to identify and quantify the confounding-free effect of Native American ancestry on the risk of overall BC and BC subtypes.…”
Section: Discussionmentioning
confidence: 99%
“…These samples were part of a previous study that aimed to analyze the association between genetic ancestry and ER/HER2/GRB7 status [ 22 ], and for this study, sample size was estimated based on the median fraction of IA ancestry for the Colombian population according to previous published data [ 23 ], using an absolute error of 5%. This research was approved by the Colombian NCI ethics committee and defined as risk-free, therefore, according to the Colombian laws, it was considered that no informed consent was required.…”
Section: Methodsmentioning
confidence: 99%
“…Oncologic anthropology is also relevant in studying the breast cancer burden of Latina/Hispanic women internationally 27–40 . Ancestry‐associated variants have been identified that predict risk from specific breast cancer phenotypes among Latina women in the United States, in Central America, and in South America.…”
Section: Oncologic Anthropology: Influence Of Germline Genetic Ancest...mentioning
confidence: 99%
“…Oncologic anthropology is also relevant in studying the breast cancer burden of Latina/Hispanic women internationally. [27][28][29][30][31][32][33][34][35][36][37][38][39][40] Ancestry-associated variants have been identified that predict risk from specific breast cancer phenotypes among Latina women in the United States, in Central America, and in South America. These studies have also found that among admixed Latina women, the extent of European ancestry increases the risk of breast cancer, whereas extent of Indigenous American ancestry decreases the risk of breast cancer.…”
Section: Oncologic Anthropology: Influence Of Germline Genetic Ancest...mentioning
confidence: 99%